Rincón recreativo para desarrollar el juego simbólico en los niños y niñas de inicial II del centro parvulario la primavera año 2015-2016 - Apugllon Apugllon, Vanesa Lucia (2017)
The problem identified at Centro de Education Inicial La Primavera, was the lack of recreational places to develop the symbolic game, through these recreational places, the children are stimulated to develop all their sensory, motor and social skills in a spontaneous and self-taught way, facilitating their learning, which is also known as a relaxation space and Stimulus so the interaction of children is totally spontaneous and natural. The objective of this project was to determine how the recreational area influences in the development of symbolic game. Inductive, deductive and analytical, methods were used for this research. The type of research was descriptive and field, the observation was the technic , an instrument the observation sheet, worked with all of populationa at about ten children and at ten girls. After the diagnosis, some results were observed. Children, boys and girls develop their skills in a significant way, in a highest percentage at 49%. It was concluded that the recreational area does influence the development of the symbolic game, so it is recommended to implement: The corners recreational activities, in order to stimulate the symbolic game, awakening the child's natural abilities, exploration, research and socialization skills-and with the help of teachers and parents, recreational areas were built.